Selection bias on intellectual ability in autism research: a cross-sectional review and meta-analysis - Russell, Ginny; Mandy, William; Elliott, Daisy; White, Rhianna; Pittwood, Tom; Ford, Tamsin (Molecular autism, 2019)
Background Current global estimates suggest the proportion of the population with autism spectrum disorder (ASD) who have intellectual disability (ID) is approximately 50%. Our objective was to ascertain the existence of selection bias due to under-inclusion of populations with ID across all fields of autism research. A sub-goal was to evaluate inconsistencies in reporting of findings. Methods This review covers all original research published in 2016 in autism-specific journals with an impact factor greater than 3. Across 301 included studies, 100,245 participants had ASD. A random effects meta-analysis was used to estimate the proportion of participants without ID. Selection bias was defined as where more than 75% of participants did not have ID. Results Meta-analysis estimated 94% of all participants identified as being on the autism spectrum in the studies reviewed did not have ID (95% CI 0.91–0.97). Eight out of ten studies demonstrated selection bias against participants with ID. The reporting of participant characteristics was generally poor: information about participants’ intellectual ability was absent in 38% of studies ( n = 114). Where there was selection bias on ID, only 31% of studies mentioned lack of generalisability as a limitation. Conclusions We found selection bias against ID throughout all fields of autism research. We recommend transparent reporting about ID and strategies for inclusion for this much marginalised group.